LANGUAGE MODIFICATION AND SUPPORTIVE ACTIONS BY AN ENGLISH TEACHER AT AN EYL CLASSROOM - Siti Hazzah Sri Rahayu (Journal of English and Education, 2013)
The paper is concerned with the analysis of how a teacher modifies his or her language in the classroom. Moreover, this study investigates what the teacher does to support his or her language in the classroom. This study was conducted in one of international kindergartens in Bandung. The data were collected through video recording. Then, the data were analyzed according to Pinter’s language modification framework (2006) and Harmer’s paralinguistic features (2002). The result shows that the teacher tended to modify her language by repeating her utterances. The teacher also supported her talk by implementing paralinguistic features, especially gestures. This study recommended that teachers should consider their choice of language carefully and support her talk by implementing paralinguistic features. Keywords:Teacher talk, language modification, supportive actions, young learners